Synthesis and Computational Investigations of Ruthenium(II) Complexes Containing Hydrazine Schiff Base Ligands - Kamalesu, S.; Swarnalatha, K.; Subramanian, R. (Journal of Applied Solution Chemistry and Modeling, 2022)
Three new heteroleptic ruthenium(II) complexes containing hydrazine schiff base as ligands were synthesized and characterized by using elemental analysis, FT-IR, 1H, 13C NMR, and mass spectroscopic techniques. FT-IR study showed that the substituted phenylhydrazine ligands behave as a monoanionic bidentate O and N donors (L) coordinate to ruthenium via the deprotonated phenolic oxygen and the azomethine nitrogen. They possess excellent thermal stabilities, evident from the thermal decomposition temperatures. Absorption, emission and electrochemical measurements were carried out and the structures of the synthesized complex were optimized using density functional theory (DFT). The molecular geometry, the highest occupied molecular orbital (HOMO), the lowest unoccupied molecular orbital (LUMO) energies, Mulliken atomic charges and molecular electrostatic potential (MEP) of the molecules are determined using B3LYP method and standard 6-311++G (d, p) basis set.